DEVELOPMENT OF THE COMPLEX-ALLOYED STEEL OF INCREASED HARDENABILITY, VISCOSITY AND HEAT-RESISTANCE FOR CUTTING PARTS OF HIGH-SPEED INSTRUMENT, OPERATING IN CONDITIONS OF HEATING UP AND DYNAMIC LOADS - V. N. Fedulov (Литьë и металлургия)
The theoretical aspects of development of the complex-alloyed steel compounds for cutting parts of high-speed instrument, particularly influence of alloying elements on its structure and characteristics are considered. It is shown that combined alloying of steel by carbon, chrome, silicon, manganese, vanadium and molybdenum in a certain proportion allows to reach the intended aim, achieving at the same time increase of solidity, impact elasticity and heat stability.